Model of 5R spatial linkage in the geometry of tori - Bil, Tadeusz; Budniak, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
The present study covers the problem of a kinematic analysis of a spatial 5R single DOF linkage. This mechanism was constructed by combining two 4R universal mechanisms presented in tori geometry (Bil, 2012). The problem can be presented as the effect of an intersection of two tori in such a manner that the circles that form these tori do not coincide (Bil, 2010; 2011; 2012; 2012).
Keywords: Bennett; Goldberg; spatial mechanism; torus; 5R mechanism